William Harris Crawford papers - Crawford, William Harris, 1772-1834.
Correspondence and other papers relating primarily to Crawford's role as U.S. minister to France, especially to negotiations surrounding the Treaty of Ghent. Also includes material relating to his tenure as U.S. secretary of the treasury and to politics in Georgia and Washington, D.C. Correspondents include John Quincy Adams, James A. Bayard, Henry Clay, Albert Gallatin, James Monroe, Richard Rush, Jonathan Russell, and Arthur Wellesley, duke of Wellington. Also includes a journal with references to Ruth Baldwin Barlow; Marie Joseph Paul Yves Roch Gilbert du Motier, marquis de Lafayette; and David Bailie Warden.
In part, photocopies and transcripts.
Diplomat and U.S. secretary of the treasury.
Collection material in English.
Keywords: Adams, John Quincy, -- 1767-1848 -- Correspondence; Barlow, Ruth, -- 1755-1818.; Bayard, James A. -- 1767-1815 -- Correspondence; Clay, Henry, -- 1777-1852 -- Correspondence; Gallatin, Albert, -- 1761-1849 -- Correspondence; Lafayette, Marie Joseph Paul Yves Roch Gilbert du Motier, -- marquis de, -- 1757-1834.; Monroe, James, -- 1758-1831 -- Correspondence; Rush, Richard, -- 1780-1859 -- Correspondence; Russell, Jonathan, -- 1771-1832 -- Correspondence; Warden, David Bailie, -- 1772-1845.; Wellington, Arthur Wellesley, -- Duke of, -- 1769-1852 -- Correspondence; United States. -- Department of the Treasury; Great Britain. -- 1814 December 24.; Diplomatic and consular service, American -- France; France -- Foreign relations -- United States; Georgia -- Politics and government; United States -- Foreign relations -- France; Washington (D.C.) -- Politics and government; Cabinet officers; Diplomats